Attitudes toward working with computers amongst South African tertiary sector users - Argirys, Loukia (My University, 2016)
The aim of the present study was to assess employees' attitudes toward working with computers. A review of previous studies conducted within the area of attitudes toward computers and attitudes toward working with computers revealed that the present study needed to condifer user-task-system characteristics and that an adequate attitude scale which examined specifically attitudes towards working with computers needed to be developed. In order to conduct the present study, a checklist was developed to assess user-task-system characteristics and an attitude toward working with computers scale was developed and validated.[Abbreviated Abstract. Open document to view full version]
Keywords: Computer literacy--South Africa; Attitude (Psychology); Banks and banking--South Africa--Data processing